IDENTIFICATION OF FACILITIES AND INFRASTRUCTURE TO SUPPORT THE TOURISM POTENTIAL OF TANA TIDUNG REGENCY - eko prihartanto; Efraim Bavo Priyana (2477 - 6165, 2023)
Tana Tidung Regency is a Regency that has potential in tourism in North Kalimantan Province. The attractions in Tana Tidung Regency are Mount Rian attractions, pine forest attractions, mangrove forest attractions, and Mahesya waterpark attractions. The purpose of this study is to analyze in order to find the object of the need for tourism facilities and infrastructure located in Tana Tidung Regency. The method used in terms of data collection is in the form of observation by the research team as respondents. The primary data in this study were interviews and questionnaires given to (PUPR Service, Tourism Office, Transportation Service, Bappeda Service, Tourist Object Visitors and the people of Tana Tidung Regency), while secondary data was sourced from journals and articles that could be clarified. The variable measurement instrument uses validity and reliability tests. The results of this study are correspondent responses based on supporting aspects of tourism supporting facilities and infrastructure in Tana Tidung Regency 1). Environmental aspects (attractive, 78.57%), 2). Cultural aspects (quite supportive, 65.60%). 3). Man-made Aspect (supporting, 68.44%), 4). Aspect of Tourism Facilities/Infrastructure (good, 70.59%), 5). Tourism Infrastructure Aspect (supporting, 72.60%).